Engineering bioactive synthetic polymers for biomedical applications: a review with emphasis on tissue engineering and controlled release. Issue 14 (4th June 2021) - Bolívar-Monsalve, Edna Johana; Alvarez, Mario Moisés; Hosseini, Samira; Espinosa-Hernandez, Michelle Alejandra; Ceballos-González, Carlos Fernando; Sanchez-Dominguez, Margarita; Shin, Su Ryon; Cecen, Berivan; Hassan, Shabir; Di Maio, Ernesto; Trujillo-de Santiago, Grissel
Abstract : We review strategies for engineering synthetic polymers from fabrication to chemical functionalization for biomedical applications. Particular emphasis is devoted to strategies related to tissue engineering and controlled release applications. Abstract : Synthetic polymers (SyPs) have found many relevant applications niches in biomedical engineering. Their mechanical properties, defined chemical structure, batch to batch consistency are attractive features that render them superior (at least in some senses) to natural polymers. However, most SyPs must be functionalized in order to properly serve for an intended biological application. Here we describe recent strategies used to functionalize SyPs for tissue engineering and related applications. We review functionalization strategies to promote cell–polymer interactions, to direct cell fate, and to induce extra-cellular matrix (ECM) (or tissue) remodeling. Besides chemical functionalization, we describe a selection of methods ( i.e., casting and particle leaching, thermally induced phase separation, electrospinning, gas foaming, and 3D printing) that have been used in recent literature to modify the architecture/topography of scafolds made of SyPs. We also review recent literature on SyPs functionalization to impart antimicrobial or conductive character and to engineer actuators for tissue engineering applications. Finally, we briefly discuss some of the trends on the engineering of SyPs ( i.e., bioinspiration, 3D bioprinting, nucleic-acid-based platforms) that are currently reshaping tissue engineering.